DESIGNING A CHARACTER EDUCATION DEVELOPMENT BASED ON ATOMIC HABIT BY JAMES CLEAR - Riza Amar Fahmi; Fathi Hidayah (International Conference on Humanity Education and Society (ICHES), 2025)
This research explains a design of character education develompent based on the bookAtomic Habits by James Clear. Character is a fundamental goal of education. Onealternative solution is to utilize recent, scientifically proven, and effective findings inthe field of character education—such as those found in the book Atomic Habits. Thisresearch is a library research study using a qualitative approach. The primary datawere obtained from the book Atomic Habits, while secondary data were sourced frombooks, articles, and other relevant documents. The data were collected throughdocumentation techniques and analyzed using content analysis by comparing,compiling, and sorting data to identify relevant information. The data validity wasensured through increased diligence and source triangulation. The findings of thisresearch show that the a design of character education development based on AtomicHabits by James Clear includes four stages: identifying the character values to bedeveloped, formulating small habits aligned with those values, applying the four lawsof behavior change, and finally, conducting monitoring, evaluation, and adjustment.